Дослідження характеристик спрацьовування індукційно-динамічного механізму - Литвиненко, Вікторія Володимирівна (НТУ "ХПІ", 2018)
Приведено конструкцію прямоходового індукційно-динамічного механізму, що застосовується в швидкодіючих брейкерах. Розроблено принципову електричну схему лабораторного стенду з дослідження індукційно-динамічного механізму та розглянуто принцип роботи схеми. Приведено опис елементів електричної схеми. Виготовлено макетний зразок індукційно-динамічного механізму та змонтовано мобільний лабораторний стенд з необхідними апаратами, закріпленими на DIN-рейці та допоміжними аксесуарами. Допоміжні деталі для монтажу елементів стенду виготовлені за допомогою сучасного 3D принтера FLASHFORGE CREATOR PRO. Отримано осцилограми перехідних процесів при спрацьовуванні індукційно-динамічного механізму, а саме: осцилограми струму в обмотці механізму та напруги на накопичувальному конденсаторі та осцилограма переміщення рухомого диску. Лабораторний стенд використовується у навчальному процесі як складова лабораторного практикуму з дисципліни "Електричні апарати".

The design of the linear-drive induction-dynamic mechanism used in high-speed breakers is presented. The research mechanism consists of a coil with leads and a moving disk. The coil of the mechanism is wound with copper tape, the disk is made of copper bus and mounted on the rod, which passes through the hole of the coil. A circuit diagram of a laboratory test bench for the study of the induction-dynamic mechanism has been developed and the principle of operation of the circuit has been considered. A description of the electrical circuit elements is given. A prototype model of the induction-dynamic mechanism was manufactured and a mobile laboratory stand was assembled with the necessary devices mounted on a DIN-rail and ancillary accessories. The high speed of the induction-dynamic mechanism is ensured by the presence of a storage capacitor, which discharges the stored energy to the mechanism coil in a relatively short time. Auxiliary parts for mounting the elements of the stand are made using a modern 3D printer FLASHFORGE CREATOR PRO. Oscillograms of transients are obtained when an induction-dynamic mechanism is triggered, namely: oscillograms of current in the mechanism winding and of voltage on a storage capacitor as well as oscillogram of moving disk displacement. The laboratory stand is used in the educational process as a component of the laboratory workshop on the discipline "Electrical Apparatus".
Research of the induction-dynamic mechanism operation characteristics
Keywords: котушка; диск; накопичувальний конденсатор; електрорушійна сила; coil; storage capacitor